PROTECTION OF PERSONAL INFORMATION IN INFORMATION SYSTEMS - Deletić, Velimir; Deletić, Milan (BizInfo Blace, 2010)
Multiorganization transparency, legal and ethical aspects and the responsibility imposed on the complex challenges not only in terms of technological information systems architecture. In addition, technological architecture must be balanced with ethical and legal standards that often do not comply with technical and technological capabilities. Generic protection mechanisms should allow the definition of standards and policies the use of personal information that will be technologically scalable. This ensures maximum utilization of technological development with a reduced risk of developing the "hole" in the system of care that can lead to abuse.